An accurate FSI-SPH modeling of challenging fluid-structure interaction problems in two and three dimensions - Sun, Peng-Nan; Le Touzé, David; Oger, Guillaume; Zhang, A-Man (Ocean engineering, 2021)
The recently developed FSI-SPH model (Sun et al., 2019c), by combining the multi-resolution δ+-SPH scheme and a Total Lagrangian SPH method, is further extended for more complex three-dimensional (3D) Fluid Structure Interaction (FSI) problems. The FSI-SPH model is strengthened with advanced numerical techniques, in which a combination of the Particle Shifting Technique (PST) and the Tensile Instability Control (TIC) is adopted to prevent flow voids induced by the tensile instability. The Adaptive Particle Refinement (APR) is used to refine particles in the boundary layer region and coarsen particles in the far-field to increase local accuracy but reduce overall computational cost. Moreover, the δ+-SPH and Total Lagrangian SPH solvers are coupled through a Modified Sequential Staggered (MSS) algorithm which, on one hand, ensures the numerical accuracy and stability and, on the other hand, improves the efficiency when magnitudes of time steps between the two solvers differ from each other significantly. In the numerical results, challenging 2D and 3D FSI cases are simulated to test the accuracy of the proposed FSI-SPH model. A new FSI benchmark with free-surface is proposed to highlight the advantage of this FSI-SPH model in simulating free-surface viscous flows. In addition, 3D effects in the FSI dam-breaking and sloshing cases are investigated. •Multi-resolution δ+-SPH model is accurately and efficiently coupled with the Total Lagrangian SPH model.•Complex three-dimensional (3D) Fluid Structure Interaction (FSI) problems are simulated and validated.•A new benchmark named FSI4 is proposed.•The 3D effects in the FSI dam-breaking and sloshing cases are highlighted.